2017
DOI: 10.4034/pboci.2017.171.22
|View full text |Cite
|
Sign up to set email alerts
|

Surface Degradation of Resin-based Materials by Pediatric Syrup Containing Amoxicillin under Erosive Challenge

Abstract: Objective: To investigate the effect of a pediatric syrup containing Amoxicillin on resin-based on the surfaces of resin-based materials under pH cycling. Material and Methods: Cylindrical samples (n=60) of a compomer (Freedom) and a microhybrid composite (TPH Spectrum) were prepared following the manufacturer's instructions. The specimens were divided into two groups and treated for 30min, twice a day, for 14 days with a pediatric syrup containing Amoxicillin, Amoxil™ 500mg/5ml (experimental group) or Distill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Augmentin® is the most frequently used broad spectrum antibiotic. Santos et al 19 also showed that pediatric syrup containing amoxicillin increased the surface roughness of compomer material. Performing oral cleaning after using this medicine, showing values close to the distilled water group when the surface roughness is taken into consideration (1.0 nm), will be appropriate.…”
Section: Discussionmentioning
confidence: 94%
“…Augmentin® is the most frequently used broad spectrum antibiotic. Santos et al 19 also showed that pediatric syrup containing amoxicillin increased the surface roughness of compomer material. Performing oral cleaning after using this medicine, showing values close to the distilled water group when the surface roughness is taken into consideration (1.0 nm), will be appropriate.…”
Section: Discussionmentioning
confidence: 94%